2013
DOI: 10.1371/journal.pone.0081423
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP3, a Transcriptional Target of Homeobox D10, Is Correlated with the Prognosis of Gastric Cancer

Abstract: Homeobox D10 (HoxD10) plays important roles in the differentiation of embryonic cells and progression of breast cancer. Our previous report revealed that insulin-like growth factor binding protein-3 (IGFBP3) was regulated by HoxD10 in gastric cancer cells; however, the functional roles and underlying mechanisms of IGFBP3 in gastric cancer remain unclear. Here, we found that the expression of IGFBP3 were upregulated after ectopic expression of HoxD10 in gastric cancer cells. Chromatin immunoprecipitation assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
3
29
0
1
Order By: Relevance
“…The downregulation of IGFBP3 we observed is consistent with reported roles as a suppressor of cell migration, tumor progression and metastasis for prostate, colorectal, gastric and endometrial cancers [32][33][34][35][36]. The type 1 insulin-like growth factor receptor (IGF1R) is overexpressed in prostate cancer (PCa; [37]) and its function in the PC3M parental cell line, PC3, is well documented, suggesting that HGF-induced IGF1BP3 downregulation in PC3M would most likely increase IGF1R responsiveness to available IGF1, and in turn enhance cell survival, proliferation and motility.…”
Section: Analysis Of Hgf Motogenic Signaling By Gene Expression Profisupporting
confidence: 91%
“…The downregulation of IGFBP3 we observed is consistent with reported roles as a suppressor of cell migration, tumor progression and metastasis for prostate, colorectal, gastric and endometrial cancers [32][33][34][35][36]. The type 1 insulin-like growth factor receptor (IGF1R) is overexpressed in prostate cancer (PCa; [37]) and its function in the PC3M parental cell line, PC3, is well documented, suggesting that HGF-induced IGF1BP3 downregulation in PC3M would most likely increase IGF1R responsiveness to available IGF1, and in turn enhance cell survival, proliferation and motility.…”
Section: Analysis Of Hgf Motogenic Signaling By Gene Expression Profisupporting
confidence: 91%
“…Nevertheless, it is too soon to exclude local IGFBP3 protein expression from being a biomarker. In gastric cancer, IGFBP3 deficiency in IHC was found to be correlated with advanced lymph node stage and poor survival (39). It is still necessary and promising to probe the relationship of local IGFBP3 expression with other clinicopathological factors and CRC patient prognosis in a larger cohort with mature survival data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Xue and collagus also indicated that IGFBP-3 can suppres some invasion factor like urokinase-type plasminogen activator (uPA) and MMP-14 (35). Harada and colleagues also showed that IGFBP-3 can induce apoptosis via IGFBP-3R in lung cancer (36).…”
Section: Discussionmentioning
confidence: 99%